A new species of Amolops (Anura: Ranidae) from Vu Quang National Park—an ASEAN Heritage Park of Vietnam - Pham, Anh Van; Hoang, Chung Van; Nguyen, Truong Quang; Nguyen, van Thi Hong; Nguyen, Thuy Thu Thi; Nguyen, Ky Danh; Thai, Toan Canh; Hoang, Ngoc Van; Pham, Cuong The (Zootaxa, 2026)
A new species of Amolops is described from Vu Quang National Park, Ha Tinh Province, North-central Vietnam based on morphological and molecular differences. Morphologically, Amolops minhlei sp. nov. is distinguishable from its congeners by a combination of the following morphological characteristics: SVL 31.8–35.8 mm in males, 36.7–45.8 mm in females; head longer than wide; vomerine teeth absent; snout long (SE/SVL 0.16–0.17 in males, 0.16 in females); tympanum distinct, round (TD/ED 0.41–0.42 in males, 0.40–0.43 in females); skin smooth; supratympanic fold indistinct; dorsolateral fold present; webbing formula I0–0II0–1/2III0–1/2IV1/2–0V; dorsum olive green or reddish brown with a few dark spots; a brown dorsolateral stripe extending from behind eye to above vent; dorsal surface of fore- and hind-limbs light grey with brown crossbars, throat, chest and belly white; males with external vocal sac and nuptial pad on finger I; and flanks grey brown with small white glandular spot. In phylogenetic analyses, the new species is strongly supported as a member of the A. monticola group. However, the new species differs from other members of the A. monticola group by 10.00–19.66% pairwise genetic divergence in the mitochondrial ND2 gene fragment and 1.56–6.67% in the mitochondrial 16S gene fragment.